Corpus de référentiels d’aide à la décision pour la résilience de la production vivrière aux risques climatiques dans la région Maritime au Togo - Komi Sanou; Mathieu Badolo (VertigO)
In western Africa, the resilience of the economic sectors to climate risks and changes is a major development challenge. A strong scientific information is essential to formulate and implement efficient and successful resilience processes. For Western Africa, and particularly for the agricultural sector, making such information available is one of the major scientific challenges in developing resilience strategies. In Togo, agriculture is one of the economic sectors particularly concerned with issues of improving resilience to climate risks and disasters. In default, the development of this sector could be heavily handicapped by the climate changes that will alter precipitation patterns and increase the frequency and the intensity of the extreme weather events. The present research aimed to provide a decision-making referential framework for improving governance and the resilience process of agriculture sector in Maritime region of Togo. The referential carried over, founds itself on ClimProspect model, is based on expert judgment method and coupled with the participative approach. The latter consisted in collecting qualitative data by means of groups of villagers. The results allowed to identify the referential of impact, vulnerabilities (V1, V2, V3 and V4), monitoring of vulnerability and resilience paths, capable of promoting spaces for dialogue between stakeholders involved in the resilience of agricultural production. Actors involved in the sector establish shared objectives of resilience, define and plan in time innovation and regularly baseline of resilience actions in this development sector.